Conservation-Based Empowerment Da'wah Spirit: Management of Welo Asri Tourism by The Muslim Community of Kayupuring Petungkriyono Pekalongan - Ahmad Hidayatullah (Prosperity: Journal of Society and Empowerment, 2022)
Da'wah should have an orientation from mere rhetoric to action, and it needs to be carried out not only in the fields of theology and Islamic education (Islamic education) but must also be realized in the form of empowerment that leads to the welfare of the people. This effort is what the Muslim community of Kayupuring Petungkriyono Pekalongan Village did by establishing the Forest Village Community Institution (LMDH) and collaborating with Perhutani to explore the potential of the forest in their area. Welo Asri Tourism Object was eventually established in the Welo river basin as a tangible manifestation of realizing their empowerment and welfare without neglecting to preserve the Petungkriyono forest. Using this type of qualitative research, Field Research, this article explores how the Muslim community's management of Welo Asri tourism is carried out by the Muslim community with a conservation-based da'wah spirit. As for the results of this study, which reviewed the three criteria for indicators of the success of Social Forestry, namely Institutional set-up (social), Forest Management (ecological), and Business Development (economics), it can be concluded that the management of Welo Asri Tourism Object can be said to have found optimal results. As an official institution, this tour is managed by LMDH Kayupuring by applying restrictions on accommodation development and management based on ecological principles. In addition, in terms of financial results, Welo Asri Tourism Object can also support 30% of the total 300 heads of families (KK) in Kayupuring Village. This condition proves that the self-help empowerment program and for them is running.